1987
DOI: 10.1159/000174223
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Electrocardiographic Monitoring in Myotonic Dystrophy (Steinert’s Disease)

Abstract: Ambulatory electrocardiographic monitoring (AEM) was performed in 22 patients (range 13–62 years; mean age 38.2 ± 12.7) with grades I, II and III of myotonic dystrophy in order to evaluate the occurrence of potentially dangerous cardiac arrhythmias and conduction disturbances. All patients had previously undergone echocardiographic examination to determine whether structure and function abnormalities were present. In 6 patients with normal resting electrocardiogram, AEM revealed: first degree A-V block (4 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…At the initial study, all patients demonstrated what we previously considered normal or near normal electro cardiographic and Holter findings [ 16], Only one of these subjects (patient 6) had abnor mal tracings at follow-up consisting of stable first-degree atrioventricular block and fre quent episodes of Mobitz type I and II sec ond-degree atrioventricular block either while awake or during sleep.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…At the initial study, all patients demonstrated what we previously considered normal or near normal electro cardiographic and Holter findings [ 16], Only one of these subjects (patient 6) had abnor mal tracings at follow-up consisting of stable first-degree atrioventricular block and fre quent episodes of Mobitz type I and II sec ond-degree atrioventricular block either while awake or during sleep.…”
Section: Resultsmentioning
confidence: 83%
“…A detailed description of techni cal methods and results of our original investigation has previously been published in this journal [16]; furthermore, 2 additional subjects were successively examined. A follow-up was possible in 21 of these 24 patients; however, telephone calls with the 3 patients not restudied identified that 2 of them (men with a mild degree of MD, aged 27 and 37 years, respective ly) with normal cardiac study at presentation had apparently unchanged clinical conditions, whereas the third patient, a 61-year-old man affected by a moderately severe form of MD, with abnormal elec trocardiographic and echocardiographic findings at first control (healed myocardial infarction) was bed ridden and his cardiac status was severely impaired.…”
Section: Methodsmentioning
confidence: 99%
“…The high incidence of paroxysmal atrioventricular block in patients with an abnormal HV interval justifies the early implantation of a cardiac stimulation device in this population 4. One of the problems is to choose the ideal time to carry out an electrophysiological study, and there are at present no clinical criteria for this,13 though Hayashi et al reported that onset of disease tended to be higher in the presence of cardiac conduction abnormalities on resting ECG 16. In our study we attempted to find a threshold of age, onset of disease, and severity of neurological involvement using receiver operating characteristic curves (not shown).…”
Section: Discussionmentioning
confidence: 94%
“…Cardiac conduction abnormalities expose patients with myotonic dystrophy to paroxysmal atrioventricular block and sudden death,2 4 13 14 and contribute to the occurrence of bundle branch block reentrant tachycardia 15. The high incidence of paroxysmal atrioventricular block in patients with an abnormal HV interval justifies the early implantation of a cardiac stimulation device in this population 4.…”
Section: Discussionmentioning
confidence: 99%
“…Another common arrhythmia is atrial fibrillation/flutter (AFib/Afl) which occurs in different studies at frequency ranging from 5–30% of cases. Studies of adult DM1 patients, using 24-h Holter monitoring (i.e., ambulatory monitoring), reported an 8 to 22% incidence of Afib/Afl in patients with severe DM1 [ 32 , 33 ]. Similar findings were reported using standard 12 lead ECGs [ 34 ].…”
Section: Ecg and Conduction Defects In Dm1mentioning
confidence: 99%